Detection of circulating tumor cells with a novel microfluidic system in malignant pleural mesothelioma. Issue 2 (8th January 2019) - Yoneda, Kazue; Kuwata, Taiji; Chikaishi, Yasuhiro; Mori, Masataka; Kanayama, Masatoshi; Takenaka, Masaru; Oka, Soichi; Hirai, Ayako; Imanishi, Naoko; Kuroda, Koji; Ichiki, Yoshinobu; Ohnaga, Takashi; et al.
Abstract : Detection of rare tumor cells circulating in the blood (CTCs) presents technical challenges. CellSearch, the only approved system for clinical use, fails to capture epithelial cell adhesion molecule‐negative CTCs such as malignant pleural mesothelioma (MPM). We have developed a novel microfluidic device (CTC‐chip) in which any Ab to capture CTCs is conjugated. The CTC‐chip was coated with an Ab against podoplanin that is abundantly expressed on MPM. Circulating tumor cell‐detection performance was evaluated in experimental models in which MPM cells were spiked in blood sampled from a healthy volunteer and in clinical samples drawn from MPM patients. The CTC‐chip showed superior CTC‐detection performance over CellSearch in experimental models (sensitivity, 63.3%‐64.5% vs 0%‐1.1%; P  <   .001) and in clinical samples (CTC‐positivity, 68.8% vs 6.3%; P  <   .001). A receiver operating characteristic (ROC) analysis showed that the CTC test provided a significant diagnostic performance in discrimination of unresectable disease from resectable disease (area under the ROC curve, 0.851; P  =   .003). The higher CTC count (≥2 cells/mL) was significantly associated with a poor prognosis ( P  =   .030). The novel CTC‐chip enabled sensitive detection of CTCs, which provided significant diagnostic and prognostic information in MPM. Abstract : Cell‐based liquid biopsy has several potential advantages over tissue biopsy, but detection of rare tumor cells circulating in the blood (CTCs) presents technical challenges. We have developed a novel microfluidic device (CTC‐chip) in which any Ab to capture CTCs can be conjugated. In the present study, the novel CTC‐chip conjugated with an Ab against a mesothelial marker (podoplanin) provided high CTC‐detection performance in experimental models and in clinical samples drawn from patients with malignant pleural mesothelioma. These results indicate that the CTC test is potentially useful in the diagnosis and treatment decision‐making for MPM patients.